Prehistoric Sources of Chert in Northern Labrador: Field Work and Preliminary Analyses - Lazenby, M.E. Colleen (ARCTIC, 1980)
The Torngat Archaeology Project is involved in a raw materials program that includes the "finger-printing" of certain lithics used by prehistoric cultures in Labrador, and the identification of their geological sources. Field work was carried out in 1978 in the Ramah and Mugford areas to sample chert outcrops and search for evidence of prehistoric quarrying and manufacturing activities. Numerous quarries and workshops were discovered in the Ramah Group, and a suite of Ramah and Cod Island chert samples was collected for analyses. Thin sections of four visually similar rock types from Labrador - Ramah chert, Cod Island chert, Saglek quarzite, and Ryan's quartz - were examined and samples of each were submitted for trace element analysis by neutron activation. Given the high purity of the cherts and the small number of samples used in the preliminary activation analysis, confident identification of and strong discrimination between the four, based on trace element concentrations, were not possible. However, thin section examination enabled identifications and differentiations to be made based on the petrographic features of each of the lithics.